The answer is: " (x − 8) (x + 3) " .
__________________________________________________________
" (x − 8) (x + 3) " are the factors of: " x² − 5x − 24 " .
_________________________________________________________
Step-by-step explanation:
__________________________________________________________
Given: "x² − 5x − 24 " ; Factor this "trinomial" expression completely.
We notice the "-5x" and the "-24 .
What factors of "-24" add up to "-5" ?
-1 + 24 ? No.
-24 + 1 ? no.
-12 + 2 = -10? No.
12 + (-2) = 12 - 2 = 10 ? No.
-3 + 8 = 5 ? No.
-8 + 3 = -5 ? Yes!
So: " (x − 8) (x + 3) " are the factors of: " x² − 5x − 24 " .
______________________________________________________